Influence of L-carnitine on litter characteristics from gilts harvested at day 40, 55, and 70 of gestation - K R Brown; B J Johnson; Michael D Tokach; J Ernest Minton; A E Brazle; T E Burkey; C N Groesbeck; C R Neill; J D Schneider; J C Woodworth; Robert D Goodband; Jim L Nelssen; et al. (Kansas Agricultural Experiment Station Research Reports, 2005)
A total of 59 gilts were used to determine the effects of supplemental L-carnitine on reproductive performance. Experimental treatments were arranged in a 2 × 3 factorial with main effects of L-carnitine (0 or 50 ppm) and day of gestation (40, 55, or 70). All gilts received a constant feed allowance of 3.86 lb/day and a top-dress containing either 0 or 88 mg of L-carnitine, starting on the first day of breeding and continuing until the day of harvest. Total litter size, total litter weight, and crown-to-rump length of fetuses were not different (P>0.10) between treatments at any gestation length. By d 70 of gestation, average fetus weight was heavier (P = 0.06) for fetuses from gilts fed L-carnitine, compared with fetuses from gilts fed the control diet. In addition, at d 70, fetal insulin-like growth factor- II (IGF-II) concentrations were lower (P = 0.09) for fetuses from gilts fed L-carnitine than for fetuses from gilts fed the control diet. Feeding L-carnitine may have decreased fetal IGF-II, therefore increasing cell proliferation and delaying cell differentiation. These results show that providing supplemental Lcarnitine to gestating gilts has beneficial effects on average fetal weight, possibly observed because of its ability to reduce fetal IGF-II concentrations.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Fetus; Gestation; Gilts; IGF-II; L-carnitine; Swine